Argumentation Profiles: A Tool for Analyzing Argumentative Strategies - Macagno, Fabrizio (Informal Logic, 2022)
An argumentation profile is defined as a methodological instrument for analyzing argumentative discourse considering distinct and interrelated dimensions: the types of argument used, their quality, and the emotions triggered. Walton’s theoretical contributions are developed as a coherent analytical and multifaceted toolbox for capturing these aspects. Argumentation schemes are used to detect and quantify the types of argument. Fallacy analysis and the assessment of the implicit premises retrieved through the schemes allow evaluating arguments. Finally, the frequency of emotive words signals the most common emotions aroused. This method is illustrated through a corpus of argumentative tweets of three politicians.